Pengaruh Current Ratio dan Perputaran Piutang Terhadap Profitabilitas (ROA) Pada Perusahaan sub sektor makanan dan minuman yang terdaftar dibursa efek Indonesia (BEI) Periode 2019 – 2022. - Sawitri , Ina; Nasution , Yuslinda; Nurfai (Mulia Pratama, 2024)
The aim of this research is to examine the influence of the current ratio and accounts receivable turnover on profitability (ROA) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019 - 2022 period, partially and simultaneously. The population in this study was 84 Food and Beverage Sub Sector companies with a sampling technique based on criteria using Purposive Sampling. The samples obtained were based on the criteria of 24 companies in the Food and Beverage Sub Sector. This type of research is quantitative. The data analysis technique used is secondary data with descriptive statistics using SPPS V.27. The research results state that the Current Ratio can partially be seen from the ttable value (3.272>1.98552) with a significance level of 0.002, which means it has a positive and significant effect on ROA. Meanwhile, Partial Receivables Turnover can be seen from the ttable value (2.142>1.98552) with a significant level of 0.035, which means it has a positive and significant effect on ROA. Simultaneously the Current Ratio and Receivables Turnover have an effect on ROA of 6.957 with a significant level of 0.002. Meanwhile, the results of the coefficient of determination (R2) show that the influence of the Current Ratio and Receivables Turnover has an effect of 0.111 on ROA. This shows that 11% of ROA is influenced by the current ratio and receivables turnover. Meanwhile, 89% can be explained by other variables not examined in this study.